Implementasi Ice Breaking Dalam Meningkatkan Motivasi Belajar Pada Mata Pelajaran SKI Di Kelas VII MTSN 1 Kota Pagar Alam - Putra Nurzaman, Irfansyah; Oktaviani, Heriyah; Fitriyani; Liana, Disti (Sekolah Tinggi Agama Islam (STAI) Bumi Silampari, 2025)
This study aims to examine the implementation of ice breaking techniques in enhancing students' learning motivation in the Islamic Cultural History (SKI) subject for Grade VII at MTsN 1 Pagar Alam City, as well as to identify supporting and inhibiting factors in applying these methods. The background of this research is based on the low learning motivation of students in SKI lessons, which are often perceived as boring and unengaging. The methodology employed is field research with a qualitative descriptive approach. Data collection techniques include observation, interviews, and documentation, with samples selected using a purposive sampling technique. The results of the study indicate that the use of ice breaking during the learning process increases students' enthusiasm, activeness, and attention throughout the teaching and learning activities. The ice breaking activities used include educational games, motivational chants, and light activities relevant to the subject matter. The conclusion of this research is that ice breaking is an effective strategy for improving students' motivation in learning SKI, particularly in Grade VII of MTsN 1 Pagar Alam City.